Performance Evaluation of MC DS CDMA using Wireless Open Access Research Platform - Suwadi Suwadi; Titiek Suryani; Devy Kuswidiastuti; Victor Hariadi; Dwi Anie Gunastuti (Department of Electrical Engineering ITS and FORTEI, 2018)
The need for reliable wireless communication systems has become an issue of communication technology development in the modern era. Multi Carrier Direct Sequence Code Division Multiple Access (MC-DS-CDMA) communication system offers superiority in efficient use of frequency spectrum through multicarrier principle as well as good information security level through direct sequence principle. WARP (Wireless Open Access Research Platform) is one type of SDR (Software Defined Radio) technology that can be programmed to create a prototype wireless communication system, one for MC DS CDMA communication system. Implementation of MC DS CDMA communication system using WARP device aims to evaluate the performance of MC DS CDMA communication system and to know how many users are able to be served simultaneously at the time of downlink compared to SC DS CDMA. The measurement results showed that the performance of BER will increase along with the increase of distance between nodes. At a distance of 3 meters the BER performance for gain 20 is 0, whereas at a distance of 5 meters for the same gain the BER performance is 0.0011. BER performance is also inversely proportional to the level of transmit power, where the greater the level of transmit power, the smaller the BER performance. At a distance of 5 meters for the transmit power level 10 obtained BER value 0.0125 and for the level of transmit power 20 obtained value BER 0.0016. In addition, MC DS CDMA communication system is more suitable for multiuser communication than SC DS CDMA with proven BER curves that are still smooth linear for data transmission of 20 users. BER performance is also the same linear down to the increase of transmit power value and Eb/No. Keywords: BER, MC DS CDMA, WARP